Cross-national Philanthropic Collaboration in The ‘Tebar Qurban 1447 H’ Program: Service-Learning And Asset-Based Empowerment in Partner Villages - Dori Chandra; Muslim Muslim; Muhamad Ashraf bin Abdul Rahiman; Taufik Hidayat; Latiful Ilham Ujung; Irgan Khairul Mahfidz; Muhammad Luqman El Hakim (ASSUNNAH PRESS, 2026)
At grassroots level, the Qurban ritual is often limited to a seasonal charitable activity that has yet to address the aspect of empowerment; consequently, a management model is required that can transform it into a means of strengthening the community. The Tebar Qurban 1447 H program is a community service initiative resulting from the collaboration of three cross-national institutions, namely STAI As-Sunnah Deli Serdang, the Arrisalah Humanitarian Care Foundation (Indonesia), and the Bayaan Association (Singapore). This article aims to analyse the implementation and impact of the program, which has been integrated into the Qafilah Dakwah activities. The implementation method combined the five-stage Asset -Based Community Development (ABCD) with a service-learning cycle, involving 15 groups of students deployed to 15 target villages in North Sumatra for approximately ten days (17–28 May 2026), culminating in the slaughter on 10 Zulhijah 1447 H (27 May 2026). The results showed the management and slaughter of 45 sacrificial animals, the meat of which was distributed to communities in the 15 villages, alongside 1,014 da’wah and educational activities benefiting 17,197 people, as well as 21 Friday sermons attended by 1,117 worshippers. This programme underscores that structured, cross-national philanthropic collaboration can transform the Qurbani ritual into an instrument of empowerment, whilst also serving as a means of instilling values and strengthening students’ soft skills—in line with the Tridharma of Higher Education.